Quality of postnatal care for mothers and neonates in Mexico: Insights from the maternal eCohort study - Martín Paredes-Cruz; Diana Perez-Moran; Svetlana V. Doubova; Catherine Arsenault; Claudio Quinzaños-Fresnedo (PLoS ONE, 2025)
Objective The study aimed to evaluate healthcare use during the postnatal period for mothers and their babies, the content of care received, mothers’ perceived quality of care, and the factors influencing these perceptions. Methods The study analyzed data from a postnatal survey conducted within the maternal eCohort at the Mexican Institute of Social Security (IMSS). The research involved 973 women aged 18–49 who were recruited following their first antenatal care visit with a family physician at 48 family medicine clinics across eight Mexican states. We described postnatal care (PNC) use, content of care and perceived quality and used Poisson multivariable regression analysis to investigate the factors influencing women’s perceptions of higher quality of care during PNC. Results 29.4% of women and 12.0% of infants had no postnatal care visits within the six weeks following hospital discharge. Among women who received PNC, 72.3% accessed services exclusively through IMSS, 17.7% utilized a combination of IMSS and other providers, and 10% relied solely on private providers. Infants received 82.4% of recommended content of care, compared to 66.7% for mothers. The median perceived quality of care among women was 25 points on a scale of 8–40. Key areas for improvement include enhancing awareness of the importance of postnatal consultations among health personnel and women, reducing waiting times, and improving the content and length of consultations. Factors associated with better perceived quality included being over 35, receiving better content of care for infants, and being treated by private providers, while lower education levels, prior pregnancies, and poor health were associated with lower perceived quality. Conclusion Improvements are needed to ensure all women and infants receive comprehensive postnatal care and to enhance patient-perceived quality.